EVALUATION OF THE ANALGESIC EFFICACY OF BALLOONLESS VERTEBROPLASTY WITH BONE CEMENT IN PATIENTS WITH OSTEOPOROTIC VERTEBRAL COMPRESSION FRACTURES - Hữu Tài, Trần; Thanh Tuyền, Trần (Journal of Health and Aging, 2026)
Osteoporotic vertebral compression fractures are a major cause of back pain and reduced spinal function in elderly patients. To evaluate the pain-relieving effectiveness of vertebroplasty in patients with osteoporotic vertebral compression fractures. A prospective study was conducted on 26 patients, assessing VAS, Macnab, and ODI scores before and after cement vertebroplasty, analyzed according to the number of fractured vertebrae. VAS scores significantly decreased from 4.85 ± 0.61 to 1.81 ± 0.49 after the procedure (p < 0.001). Macnab and ODI scores also improved markedly, with pain relief observed even in patients with multiple fractured vertebrae. Vertebroplasty is a minimally invasive procedure that effectively reduces pain and improves spinal function in patients with one or multiple osteoporotic vertebral fractures.